Calculation of loading-induced tendon slip in beams prestressed with external tendons. Part I: Experiment - Diep, Bui Khac; Quang, Lam Huu (Vietnam Journal of Mechanics, 2006)
This study consists of two parts, in which both experimental and numerical studies on externally prestressed concrete beams were investigated. In Part I, three identical beams of T-shaped section prestressed with external tendons have been tested to failure to investigate the effects of geometry of the applied load on flexural behavior of externally prestressed concrete beams. The tendon slip at deviators was also monitored in order to examine the evolution of stress in the external tendons. Test results were presented with emphasis on the effects of geometry of applied load and tendon slip at deviators.